Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1161/01.str.0000170709.95185.b1
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Clinical Outcome of Pediatric Moyamoya Disease With Postoperative Basal/Acetazolamide Stress Brain Perfusion SPECT After Revascularization Surgery

Abstract: Background and Purpose-We evaluated whether basal/acetazolamide stress brain perfusion SPECT performed after revascularization surgery can predict the further clinical outcome of patients with pediatric moyamoya disease. Methods-A total of 77 (31 males, 46 females, age 6.6Ϯ3.2 years) patients with postoperative pediatric moyamoya disease who underwent basal/acetazolamide stress brain perfusion SPECT 6 to 12 months after revascularization surgery and who were followed-up Ͼ12 months after SPECT were included. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
75
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(75 citation statements)
references
References 21 publications
0
75
0
Order By: Relevance
“…Using acetazolamide and single positron emission CT, So et al compared pre-and postrevascularization CVR studies in clinically symptomatic children with moyamoya disease. 9 They found that patients with abnormal preoperative CVR demonstrated improvement in both clinical status and CVR after revascularization, likely due to the augmented cerebral blood flow. Interestingly, the authors also found that patients with persistent reductions in CVR postoperatively were found to be at a higher risk for developing ischemic attacks and recommended reoperating 9 if that were the case.…”
Section: Discussionmentioning
confidence: 98%
“…Using acetazolamide and single positron emission CT, So et al compared pre-and postrevascularization CVR studies in clinically symptomatic children with moyamoya disease. 9 They found that patients with abnormal preoperative CVR demonstrated improvement in both clinical status and CVR after revascularization, likely due to the augmented cerebral blood flow. Interestingly, the authors also found that patients with persistent reductions in CVR postoperatively were found to be at a higher risk for developing ischemic attacks and recommended reoperating 9 if that were the case.…”
Section: Discussionmentioning
confidence: 98%
“…Noninvasive imaging modalities such as perfusion MR imaging, single-photon emission CT, and positron-emission tomography can demonstrate secondary hemodynamic changes. [1][2][3][4]12,[21][22][23][24][25][26][27] However, these methods show only overall cerebral perfusion changes and cannot directly visualize fine parenchymal neovascularization itself following the operation.…”
Section: Discussionmentioning
confidence: 99%
“…Quantification of CVR using basal/acetazolamide stress SPECT has been reported previously using ROI or SPAM [8,10]. Moreover, objective image quantification using SPAM has been widely studied in PET data such as 18 F-FP-CIT PET for dopamine transporter imaging [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, objective image quantification using SPAM has been widely studied in PET data such as 18 F-FP-CIT PET for dopamine transporter imaging [18,19]. Although SPAMbased quantification provided the objective parameters, the previous methods were descriptive and did not preserve anatomical information [8,10]. Furthermore, a relatively small sized regional decreased CVR could not be assessed using a SPAM-based descriptive parameter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation